2011
DOI: 10.1111/j.1540-6210.2011.02432.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at Comparative Public Administration: Trends in Research and an Agenda for the Future

Abstract: Intensified globalization, especially the necessity to learn more about how administrative reforms work effectively in different cultural contexts, requires public administration research to embrace comparative perspectives. How well is the field advancing in that direction? This article presents the results of a content analysis of 151 comparative public administration articles from 2000 to 2009. Results indicate that comparative research is building on theory and empirical research, making use of purposive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 34 publications
0
52
0
Order By: Relevance
“…Reviews of the public administration research suggest mixed success in responding to Dahl's call for more studies to determine how the operation of public administration may vary by national and social setting. Although there seems to be increasing recognition of the importance of studying context and culture, most of the existing research continues to be conducted in the United States and United Kingdom (Fitzpatrick et al ; O'Toole and Meier ). Even among the growing comparative literature, culture did not appear as a major concept in more than 60 percent of recently published articles (Fitzpatrick et al ).…”
Section: Dahl's Three Problems Of Public Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews of the public administration research suggest mixed success in responding to Dahl's call for more studies to determine how the operation of public administration may vary by national and social setting. Although there seems to be increasing recognition of the importance of studying context and culture, most of the existing research continues to be conducted in the United States and United Kingdom (Fitzpatrick et al ; O'Toole and Meier ). Even among the growing comparative literature, culture did not appear as a major concept in more than 60 percent of recently published articles (Fitzpatrick et al ).…”
Section: Dahl's Three Problems Of Public Administrationmentioning
confidence: 99%
“…Although there seems to be increasing recognition of the importance of studying context and culture, most of the existing research continues to be conducted in the United States and United Kingdom (Fitzpatrick et al ; O'Toole and Meier ). Even among the growing comparative literature, culture did not appear as a major concept in more than 60 percent of recently published articles (Fitzpatrick et al ). That said, there are areas in which research has begun to discover the generalities that transcend national boundaries as well as identify important differences produced by cultural and historical factors.…”
Section: Dahl's Three Problems Of Public Administrationmentioning
confidence: 99%
“…Concern for the inextricability of defining questions such as these in public administration is coming to the fore in disciplinary dialogue. Fitzpatrick et al () propose that the study of administrative reform (including police reform) in an era of increasingly complex intercultural and intergroup problems requires public administration research to build on theory and research using a mix of causal, descriptive, exploratory, and critical methods. Raadschelders () argues that the “wickedness” of administrative challenges (such as racialized police violence) requires correspondingly robust but nuanced analytical methods.…”
Section: Resultsmentioning
confidence: 99%
“…Such approaches are likely to expand the use of qualitative methods to complement quantitative methods (Durant 2015 ). Greater use of mixed methods is precisely what Fitzpatrick et al ( 2011 ) identified as both a trend and an imperative to obtain in-depth understanding of the variables and interactions being explored in comparative research.…”
Section: Greater Attention To History and Culturementioning
confidence: 99%